2013
DOI: 10.1603/en13166
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal Pattern and Dispersion of Adult and Nymph Stink Bugs (Hemiptera: Pentatomidae) in Wheat and Corn

Abstract: Euschistus servus (Say) can develop a generation on wheat, Triticum aestivum L., before moving to corn, Zea mays L., where it can be a pest. Because effective management methods are unknown, this study sought to describe the spatial distribution and dispersal of E. servus in the wheat and corn interface. In addition, Oebalus pugnax (F.) densities were documented in both crops. Wheat fields adjacent to the corn were sampled before harvest and stink bugs were marked using a product containing egg whites. Dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…On the other hand, spatial structures arising due to due to biotic processes are expected to occur at medium to fine spatial scales [ 5 , 54 , 67 69 ]. The lack of spatial patterns at fine scales suggests that the influence of biotic processes such as semio-chemical aggregation [ 40 ] or dispersal [ 49 , 50 , 70 ] on the abundances of H . halys and the native stink bugs may be localized (fine scales).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, spatial structures arising due to due to biotic processes are expected to occur at medium to fine spatial scales [ 5 , 54 , 67 69 ]. The lack of spatial patterns at fine scales suggests that the influence of biotic processes such as semio-chemical aggregation [ 40 ] or dispersal [ 49 , 50 , 70 ] on the abundances of H . halys and the native stink bugs may be localized (fine scales).…”
Section: Discussionmentioning
confidence: 99%
“…Movement from wheat to maize was not consistent between the years and may have been influenced by factors such as variations in weather, timing of wheat harvest or other available alternative hosts (Reisig et al, 2013).…”
Section: Off-crop Areas As Refuge For the Pestmentioning
confidence: 95%
“…Crop-to-crop dispersal of stink bug species has been reported for many cropping systems [ 21 , 22 , 23 , 24 , 25 ]. Although these studies are based on seasonal abundance or spatial distribution of stink bugs in adjoining crops, three mark-recapture studies have demonstrated direct movement of stink bugs from one crop to another [ 26 , 27 , 28 ]. For native species, as well as H. halys , stink bugs exhibit a pronounced edge effect during dispersal in crops [ 24 , 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies are based on seasonal abundance or spatial distribution of stink bugs in adjoining crops, three mark-recapture studies have demonstrated direct movement of stink bugs from one crop to another [ 26 , 27 , 28 ]. For native species, as well as H. halys , stink bugs exhibit a pronounced edge effect during dispersal in crops [ 24 , 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Previous studies have indicated that stink bug adults move from non-crop host plants into nearby crop field edges [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%